One-year changes in axial length and refraction in children using low-level red light and distant-image screen for myopia control: a randomized controlled trial - Yang, Ke; Wang, Yuhan; Li, Xiaoxia; Liu, Sumeng; Shi, Hui; Qiao, Liya (Frontiers in Medicine, 2025)
ObjectiveTo assess the efficacy and safety of 650-nm low-level red light (RL) and distant-image therapy (DIT) for myopia.MethodsA randomized clinical trial. Children aged 8–10 years with a spherical equivalent error (SER) ranging from −1 to −1.5 diopters (D) were enrolled, and were randomly allocated to the following group: RL, DIT, RL + DIT, and control in a 1:1:1:1 ratio. The primary outcomes were changes in SER and axial length (AL).ResultsOne hundred and sixteen children randomized, girls accounted for 45.69% (53/116). The median one-year changes in SER were 0.21D (inter-quartile range, IQR: −0.03D to 0.46D), −0.06D (−0.32D to 0.19D), −0.08D (−0.31D to 0.14D), and −0.30D (−0.51D to −0.09D), respectively, for the RL + DIT, RL, DIT, and the control group. The median one-year changes in AL were 0.04 mm (−0.03 mm to 0.13 mm), 0.05 mm (−0.03 mm to 0.14 mm), 0.30 mm (0.22 mm to 0.37 mm), and 0.42 mm (0.35 mm to 0.49 mm), respectively, for the RL + DIT, RL, DIT, and the control group. Fundus photographs revealed no retinal changes across all groups.ConclusionParticipants who underwent daily 650-nm low-level red light therapy combined with distant-image screen intervention for 12 months demonstrated a significant deceleration in myopia progression, with 79.3% exhibiting potential for reversal of myopia. No safety concerns were identified through OCT and fundus photography.Clinical trial registrationClinicalTrials.gov, NCT06683287.